Marketing Mix and Service Choice in Photography MSMEs: The Mediating Role of Branding and the Moderating Role of Price - Nurcahyati, Putri; Prastowo, Sugeng Lubar; Atichasari, Anna Sofia (PERFECT EDUCATION FAIRY, 2025)
This study examines how elements of the marketing mix influence consumer decisions in photography services, with particular attention to the mediating role of branding and the moderating role of price. A quantitative cross-sectional survey was conducted with 230 users of Fannani Photo services, selected through purposive sampling. Data were collected using a structured Likert-scale questionnaire and analyzed with structural equation modeling to assess direct, mediating, and moderating effects. The findings reveal that product quality, branding, and price significantly shape service decisions, while visual promotion and service quality do not exert direct effects but influence branding, which in turn mediates the relationship between product quality and consumer choice. Moreover, price strengthens the effects of product quality and visual promotion, though not service quality, on decision-making. The study contributes theoretically by integrating branding and price into the marketing mix framework, providing clarity to inconsistent findings in prior research, and offers practical insights for creative MSMEs to enhance product quality, build consistent branding strategies, and leverage price as a competitive advantage in the digital marketplace.